2020
DOI: 10.3390/v12070738
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Arginine-Rich C-Terminal Domains of the Hepatitis B Virus (HBV) Core Protein as a Fine Regulator of the Interaction between HBc and Nucleic Acid

Abstract: The morphogenesis of Hepatitis B Virus (HBV) viral particles is nucleated by the oligomerization of HBc protein molecules, resulting in the formation of an icosahedral capsid shell containing the replication-competent nucleoprotein complex made of the viral polymerase and the pre-genomic RNA (pgRNA). HBc is a phospho-protein containing two distinct domains acting together throughout the viral replication cycle. The N-terminal domain, (residues 1–140), shown to self-assemble, is linked by a short flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 118 publications
(284 reference statements)
1
29
0
Order By: Relevance
“…However, this functional separation of HBc is over simplified, as different studies have shown that NTD plays a role in DNA synthesis and, conversely, CTD participates in capsid assembly [ 32 , 33 ]. CTD is highly basic and undergoes dynamic phosphorylation and dephosphorylation, which regulate many HBc functions including pgRNA encapsidation, reverse transcription, capsid stability, and intracellular trafficking [ 34 , 35 , 36 , 37 ].…”
Section: Intracellular Transport and Nuclear Importmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this functional separation of HBc is over simplified, as different studies have shown that NTD plays a role in DNA synthesis and, conversely, CTD participates in capsid assembly [ 32 , 33 ]. CTD is highly basic and undergoes dynamic phosphorylation and dephosphorylation, which regulate many HBc functions including pgRNA encapsidation, reverse transcription, capsid stability, and intracellular trafficking [ 34 , 35 , 36 , 37 ].…”
Section: Intracellular Transport and Nuclear Importmentioning
confidence: 99%
“…In the first model, HBV capsids are believed to be responsible for NPC docking and genome delivery. Indeed, the CTD region, which is highly conserved between all genotypes, contains nuclear localization signal (NLS) sequences that have been shown to be functional when using NLS defective SV40 large T antigen as a reporter for subcellular localization or by studying the impact of mutations on HBc subcellular localization [ 35 , 43 , 44 ]. The role of these sequences in nuclear trafficking was further confirmed in the context of an assembled capsid by performing competition experiments for NPCs binding with peptides corresponding to NLS, using digitonin-permeabilized cells, or by studying capsid subcellular localization in hepatoma cells cotransfected with a vector coding HBc containing mutations in the putative NLS and viral polymerase [ 43 , 44 , 45 ].…”
Section: Intracellular Transport and Nuclear Importmentioning
confidence: 99%
“…The N -terminal domain of HBc is mainly α-helical and assembles into dimers, which form protruding spikes at the capsid surface [ 10 , 11 , 12 ]. The C -terminal domain is largely disordered and contains several phosphorylation sites [ 13 ] and an arginine-rich domain (ARD) that together regulate genome interaction (reviewed in [ 14 ]). The capsid accommodates the viral polymerase and a viral, partially double-stranded DNA genome of 3.2 kb.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleocapsid migrates towards the nucleus thanks to nuclear localisation signals carried by the HBc antigen. Through interactions with nuclear transport receptors and adaptor proteins of the nuclear pore complex, the capsids eventually disintegrate permitting the release of both core capsid subunits and of the relaxed circular HBV DNA (rcDNA) genome 13 . HBV DNA then enters the nucleus.…”
Section: Hepatitis B Virus and Hepatocellular Carcinomamentioning
confidence: 99%